Different Alternatives for Topics and Foci: Evidence from Indefinites and Multiple wh* - Hinterwimmer, Stefan; Repp, Sophie (Proceedings of Sinn und Bedeutung, 2019)
In gapping, topical indefinites as well as wh-phrases can contrast with surface-identical antecedents if the contrast involved is the first of the two (or more) contrast pairs in the gapping coordination. This is not possible for most other types of expressions. We argue that both topical indefinites and wh-phrases introduce a discourse referent with a fixed address, on the basis of which referents introduced by surface-identical expressions can be contrasted. For the indefinites, we argue that the first contrast pair is a pair of contrastive topics which can, at the same time, be a pair of aboutness topics. These introduce individual addresses (Reinhart 1981). For wh-phrases we follow the assumption that they introduce discourse referents by presupposition. Multiple wh-interrogatives then introduce functions by presupposition whose domain is provided by the first wh-phrase. The function is specified by giving its extension, i.e. the respective pair-list.